2011
DOI: 10.1097/sle.0b013e31820660fc
|View full text |Cite
|
Sign up to set email alerts
|

A Calcified Foreign Body in the Bladder due toaDisplacedTack

Abstract: We report a rare complication caused by a displaced tack after laparoscopic incisional hernia repair. A 41-year-old woman treated 11 months earlier for a suprapubic incisional hernia (Pfannenstiel laparotomy) received a laparoscopic repair with a bilaminar mesh fixed with tacks. Seven months later, she presented miccional irritative symptoms and chronic lower abdominal pain. Leucocyturia and microhematuria were present, and computerized tomography showed 2 calcified nodules in the bladder wall. Cystoscopy conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…4,17 In the case of tack fixation, significantly decreased operative time has been reported, 18 yet there are also isolated case reports of severe postoperative complications such as small-bowel obstruction and perforation, 1921 chronic neuropathic pain, 22 and other serious complications from tack displacement. 23,24 Recently, both suture and tack fixation in ventral hernias have been evaluated and shown to have nonsignificant differences in postoperative pain. 14 However, no such analysis has been conducted in UHR.…”
Section: Introductionmentioning
confidence: 99%
“…4,17 In the case of tack fixation, significantly decreased operative time has been reported, 18 yet there are also isolated case reports of severe postoperative complications such as small-bowel obstruction and perforation, 1921 chronic neuropathic pain, 22 and other serious complications from tack displacement. 23,24 Recently, both suture and tack fixation in ventral hernias have been evaluated and shown to have nonsignificant differences in postoperative pain. 14 However, no such analysis has been conducted in UHR.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous literature has reported laparotomy for surgical removal of migrated mesh. 3 , 4 Although Feliu et al reported laparoscopic partial cystectomy for removal of a mesh protrusion after incisional hernia repair, 5 as yet there are no reports of laparoscopic partial cystectomy to remove migrated mesh after inguinal hernioplasty. In the present case, tight adhesion on the right hypogastrium and displacement of the bladder made a laparoscopic approach difficult.…”
Section: Discussionmentioning
confidence: 99%